Modern Political Participation Online vs Offline: New Opportunities — Previous Activity? - D. I. Kaminchenko (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2020)
The paper is devoted to the study of the features of political participation in the modern information society. In the context of the rapid digitalization of the political space, the analysis of existing and emerging forms of political participation is of particular relevance.The aim of the paper is to study the impact of an individual’s internal attitudes on his/her willingness to participate in socially significant events, both online and offline. The influence of internal attitudes of individuals is considered in the paper through the prism of two factors: the perception of social media as the main channel for the expression of civic interests (perception factor) and people’s attitude to the idea of the possibility of a single political leader appearing in social media space (leadership factor).Poll among students was chosen as the main applied research method, since students are an active users of modern social media.The poll results show that almost half of active users of social media are ready to participate in social processes both online and offline. In addition, the vast majority of respondents perceive the Internet platforms of modern social media as the main channel and mechanism for expressing civic activity. The poll results also showed that half of active users deny the possibility of a single political leader appearing in the social media space (although there is a large proportion of those who, on the contrary, agree with this idea — more than a third of all respondents). Cross-analysis of the poll data confirmed the assumption indicated in the work, according to which the individuals perception of social media as a communicative channel effective for the purpose of civic participation, contributes to their readiness to participate in socially significant events online. At the same time, the study of the impact of the leadership factor on individuals’ readiness for various forms of political participation did not form an unambiguous opinion on the nature of this impact and requires further study. This study demonstrates that activity in social media does not contribute to the socio-political passivity of their users.